Premature release of action sequences in adolescent male rats - Marini, Micaela Betsabé; Belluscio, Mariano Andrés; Murer, Mario Gustavo; Martínez, María Cecilia (Frontiers in Behavioral Neuroscience, 2026)
Adolescence is a period of transition from childhood to adulthood in which subjects exhibit characteristic behaviors, such as increases in impulsivity, social interactions, novelty-seeking and risk-taking behaviors. Previous studies have shown that adolescents often respond prematurely in operant tasks, but it remains unclear whether this behavior reflects general hyperactivity, cognitive impairments, or if it is a specific form of impulsivity. Here, we trained male and female adolescent and adult Long-Evans rats in a rewarded operant task that required withholding an action sequence for a 2.5 s waiting time. Adolescent males exhibited significantly more premature responses than females or adults, despite achieving similar reward rates. To test whether this behavior was associated with other traits, we assessed locomotor activity in the Open Field and recognition memory in the Y-maze. Locomotor activity and memory performance were comparable between groups, indicating that the increased premature responding observed in adolescent males was not readily explained by differences in general activity levels or cognitive performance. Together, these findings suggest that impulsive responding during adolescence shows a sex-dependent expression and reflects a distinct behavioral component within the context of this task, rather than belonging to broader behavioral differences. Understanding the specificity of adolescent impulsivity may provide insights into vulnerability to risk-taking and psychiatric disorders during adolescence.